Nursing students' and lecturers' experiences of learning at a university-based nursing student–run health clinic. Issue 4 (4th July 2019) - Albinsson, Gunilla; Elmqvist, Carina; Hörberg, Ulrica
ABSTRACT: This article aims to describe the phenomenon of learning at a university-based nursing student–run health clinic, as experienced by student nurses and lecturers. The study is based on a reflective lifeworld research approach founded on continental philosophy. Eight group interviews were conducted with 38 student nurses and 5 lecturers. The data were explored and analysed for meaning. The results show that learning is supported by a permissive learning environment that builds on both individual and common learning as well as equal relationships within the student group, in relation to the visitors at the health clinic and, to a certain extent, in relation to the lecturers. The most significant finding is that reflective, development-oriented learning takes place when the students, supported by each other and their lecturers, reflect on how to relate to problems and situations. A situation-based learning approach is thus shown to create the prerequisites for lecturers being nearby, reflective dialogue partners but also supervisors in situations where the students ask for support and guidance.